Assessing the effect of health status on multidimensional poverty among older adults: the Chinese longitudinal healthy longevity survey - Zhou, Lulin; Zhu, Change; Walsh, Christine A.; Zhang, Xinjie (Frontiers in Public Health, 2023)
Background: To explore the association between health status (physical, mental, and self-rated health) and multidimensional poverty (subjective and objective poverty) in older adults. Method:Panel binary logit regression approach was applied to four waves of CLHLS data (2008, 2011, 2014, and 2018). In total,1445 individuals were included after data cleaning. Results: The mean values and proportion of physical, mental, and self-rated health are 5.73 (87.42%), 0.93 (93.06%), and 3.46(86.7%), respectively and mean values and proportion of subjective and objective poverty are 0.19 (18.51%) and 0.21(21.4%). In addition, physical, mental, and self-rated health was all found to be associated with subjective poverty among older adults (r=-0.181, r=-0.630, r=-0.321, P<0.05), that is the better the physical, mental, and self-rated health, the lower the probability of subjective poverty. A comparable connection between self-rated health and objective poverty also exists (r=-0.157, P<0.05). Furthermore, medical expenditure played a mediation role in the association between health status and poverty of older adults. Conclusion: In order to effectively alleviate the poverty of older adults, strategies should be taken to improve the health level of older adults, especially the physical and mental health of advanced-aged older adults, and the self-rated health of middle-aged older adults. Furthermore, social security and pensions should be further developed to adequately reimburse medical expenditures.